Analysis of sexist humour content in Lapor Pak! on Trans7 television - Al Aqilah, Laila Syahar Zainab; Maryani, Eni; Aristi, Nindi (Universitas Padjadjaran, 2025)
Background: Sexist humour in the mass media has a significant impact on gender perceptions in society, especially for women who are often victims of real actions. Purpose: This research aims to understand the meaning of humour that contains sexist elements towards women using message content analysis. Methods: This study uses a qualitative descriptive method with content analysis from Krippendorf. The data collection process is carried out through observation techniques, with an emphasis on the analysis of the content of the material or materials, such as text, images, audio or video. The use of this technique is expected to provide comprehensive and in-depth data on sexist humor in the comedy program